An overview of applications of PEEK polymer in prosthodontics. - Ashraf, Mohammed Cheruvu; Sujesh, M; Ravikumar, C; Rajanikanth, A; Duggineni, Chalapathi Rao; Sunitha, K (International Journal of Dental Materials, 2022)
The rapid evolution of computer-aided design and computer-aided manufacturing (CAD-CAM) led to the introduction of newer materials that could be precisely milled for the fabrication of dental prostheses. PEEK (PolyEtherEtherKetone) has been explored for a number of applications for clinical dentistry, including removable dental prostheses, fixed dental prostheses, implant-supported prostheses, resin-bonded fixed dental prostheses and implant-retained overdentures. The major beneficial property of PEEK is its lower Young's modulus, and as elastic as bone, providing a cushioning effect and reduction of stress transferred to abutment teeth. It is a material with high biocompatibility, good mechanical properties, high-temperature resistance, chemical stability, polishability, good wear resistance, and high bond strength with luting cements. Further, PEEK is also recommended for a wide range of CAD-CAM fabricated fixed and removable prostheses, fabrication of occlusal splints, intra-radicular posts, implant abutments and provisional restorations. PEEK material shows a property of radiolucency, which is advantageous for the evaluation of both osseointegration and tissue surrounding the implant on computed tomography. Considering these properties, PEEK is increasingly being used in implantology.